Structural holes and social entrepreneurs as altruistic brokers - René Chester Goduscheit; Dmitry Khanin; Raj V. Mahto; William C. McDowell (Journal of Innovation & Knowledge (JIK), 2021)
We propose that social entrepreneurs may act as altruistic brokers helping their beneficiaries patch the structural holes that separate the disenfranchised and marginalized individuals and groups from the opportunities, resources, and capabilities available to more privileged actors. We test our model on a database of social entrepreneurs that received funding from the Schwab Foundation and Ashoka. Our case analysis and frequency analysis performed in NVivo shows that social entrepreneurs' institutional work comprises: (1) bridging: helping beneficiaries gain access to resources and opportunities; (2) enabling: helping beneficiaries develop capabilities; and (3) bonding: helping beneficiaries form cohesive networks. Furthermore, some of these key types of institutional work may take the lead depending on various contextual factors so that either bridging, enabling, or bonding may become dominant.
Keywords: 650; altruistic brokers; bridging; enabling; bonding; Social innovation